2016
DOI: 10.1021/jacs.6b05187
|View full text |Cite
|
Sign up to set email alerts
|

Composition Tunability and (111)-Dominant Facets of Ultrathin Platinum–Gold Alloy Nanowires toward Enhanced Electrocatalysis

Abstract: The ability for tuning not only the composition but also the type of surface facets of alloyed nanomaterials is important for the design of catalysts with enhanced activity and stability through optimizing both ensemble and ligand effects. Herein we report the first example of ultrathin platinum-gold alloy nanowires (PtAu NWs) featuring composition-tunable and (111) facet-dominant surface characteristics, and the electrocatalytic enhancement for the oxygen reduction reaction (ORR). PtAu NWs of different bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 66 publications
4
73
1
Order By: Relevance
“…5)Currently, most of the reported works are based on ex situ techniques, which only give the characterization results of OER catalysts before and after electrochemical measurements but cannot provide the structural evolution information during the OER process. Therefore, in situ techniques are desirable for characterizing the structure–activity relationships of the catalysts 124,125. The combination of in situ techniques, theoretical calculation approaches, and the electrochemical measurements is an effective strategy to unravel the reaction mechanism and hence guide the rational design of efficient OER electrocatalysts. 6)Currently, most of the reported non‐noble‐metal‐based OER electrocatalysts are evaluated in alkaline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…5)Currently, most of the reported works are based on ex situ techniques, which only give the characterization results of OER catalysts before and after electrochemical measurements but cannot provide the structural evolution information during the OER process. Therefore, in situ techniques are desirable for characterizing the structure–activity relationships of the catalysts 124,125. The combination of in situ techniques, theoretical calculation approaches, and the electrochemical measurements is an effective strategy to unravel the reaction mechanism and hence guide the rational design of efficient OER electrocatalysts. 6)Currently, most of the reported non‐noble‐metal‐based OER electrocatalysts are evaluated in alkaline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Tuning the geometry / dimension of Pt‐based catalysts represents another effective strategy to improve the performance/durability by varying the symmetry and surface area. For example, 1D jagged Pt nanowires (J‐PtNWs) and {111} facet‐dominant PtAu NWs show enhanced ORR electrocatalytic performance over the nanoparticle counterparts. In particular, the unique design of J‐PtNWs (Figure G,H) simultaneously featuring a highly jagged surface topology to ensure ultrahigh SA of 10.95 mA cmPGM2 at 0.9 V versus RHE for ORR; and the 1D geometry is beneficial for retaining the stability of ultrafine (≈2 nm) nanostructures under electrochemical reactions and ensuring more efficient charge transport from the catalytic active sites to external electrodes, leading to better Pt utilization efficiency and unprecedented ECSA up to 120 m 2 g −1 , together delivering a record high MA of 13.6 A mgPGM1 at 0.9 V versus RHE (Figure ), along with enhanced stability.…”
Section: Nanoscale Structure Design For High‐performance Pt‐based Orrmentioning
confidence: 99%
“…The ORR activity was enhanced against the surface strain induced by the lattice mismatch between the Pt shell and the PtCo alloy core interface structures . Moreover, with respect to shape controlling, Chang et al reported the first example of ultrathin PdAu alloy nanowires featuring composition‐tunable and (111) facet‐dominant surface characteristics, and the electrocatalytic enhancement for the ORR . According to Beermann et al, the shape‐controlled octahedral PtNi alloy nanoparticles exhibited remarkably high activities for the electroreduction of molecular oxygen (ORR), which makes them fuel‐cell cathode catalysts with an exceptional potential .…”
Section: Trends In Quantum Mechanics Computation Approach For Highly mentioning
confidence: 99%
“…[42] Moreover, with respect to shape controlling, Chang et al reported the first example of ultrathin PdAu alloy nanowires featuring composition-tunable and (111) facet-dominant surface characteristics, and the electrocatalytic enhancement for the ORR. [43] According to Beermann et al, the shape-controlled octahedral PtNi alloy nanoparticles exhibited remarkably high activities for the electroreduction of molecular oxygen (ORR), which makes them fuel-cell cathode catalysts with an exceptional potential. [44] Wang et al proposed that the conformal deposition of Pt as ultrathin shells on facet-controlled Pd nanocrystals offers a great opportunity to enhance the catalytic performance while reducing the loading.…”
Section: Improving the Catalytic Activity By Combining Experiments Wimentioning
confidence: 99%